Genetic Connectivity and Diversity of a Protected, Habitat-Forming Species: Evidence Demonstrating the Need for Wider Environmental Protection and Integration of the Marine Protected Area Network - Mackenzie, Clara L.; Kent, Flora E. A.; Baxter, John M.; Gormley, Kate S. G.; Cassidy, Andrew J.; Sanderson, William G.; Porter, Joanne S. (Frontiers in Marine Science, 2022)
Modiolus modiolus (horse mussel) reefs are an example of marine biodiversity hotspots of high conservation importance. Due to historical destruction and slow rates of recovery, the habitat is considered threatened and/or declining under the OSPAR Convention for the Protection of the Marine Environment of the North-East Atlantic 1992, and therefore incorporated into the conservation legislation of several countries. An analysis of genetic connectivity and diversity of nine M. modiolus reefs across Scotland, both within and outside of Marine Protected Areas (MPAs), was undertaken using 12 newly developed microsatellite markers. Analyses indicated moderate to high levels of genetic connectivity between all populations and significantly low genetic variance among populations. Generally, a lack of spatial genetic structure was determined though several populations were highlighted as potentially genetically separated. Structure and connectivity results were largely corroborated by network visualization which additionally identified several potentially key populations. All populations showed departure from Hardy–Weinberg Equilibrium (HWE) and positive inbreeding coefficients, suggesting reduced genetic diversity and/or reflecting the high frequency of null alleles observed across populations. However, allelic richness was uniformly high across all reefs compared to previously reported results for the habitat. Results broadly suggest that an open system of M. modiolus populations exists in Scottish waters and align with conclusions from prior larval dispersal modeling. Findings highlight that neither M. modiolus populations nor the MPAs where they are found should be considered discrete, independent entities and support the protection of features within MPAs in concert with non-designated areas and across varying spatial scales. It is proposed that potential for greater protection exists if all relevant Scottish MPAs, i.e., both those where M. modiolus reefs are a designated feature and those that host M. modiolus reefs, had statutory restrictions on all activities that cause damage to the sea bed. Such protection may facilitate the support of vulnerable populations by more resilient populations, particularly under climate change. Furthermore, given that a large number of unprotected M. modiolus populations may be important components in the interdependent system of reef populations, supplementary genetics studies informed by larval dispersal modeling are recommended to identify further key populations for safeguarding.